HYGIENIC ASSESSMENT OF THE CONDITIONS OF EDUCATION IN THE PREPARATORY GROUPS OF PRESCHOOL INSTITUTIONS - Khusanova, N.F.; Shaykhova, G.I. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
an objective hygienic assessment of the conditions of training and education in children’s educational institutions using new approaches. Material and methods: the main factors determining the hygienic state of preschool educational institutions were the land plot, the building, the sanitary equipment and its condition, the educational process. Each of these factors contains from 5 to 12 significant indicators. The following criteria were used to quantify each indicator: good - meets the hygienic rate of 100%; satisfactory - compliance at 70-89.9%; unsatisfactory - compliance by 50-69.9%. Results: thanks to the use of an improved method of assessing the state of children’s educational institutions, an objective quantitative and qualitative characteristic of each factor will be obtained, which will enable us to make an operational decision to manage risk factors aimed at promoting the health of young children.